KEPERCAYAAN DIRI DENGAN KESIAPAN KERJA PADA SISWA SMKN 1 KENDARI - Muhammad, Fadel; Siregar, Nani Restasi; Marhan, Citra (Jurusan Psikologi FKIP Universitas Halu Oleo, 2024)
Self-confidence is a personality in the form of belief in the abilities and skills possessed and manifested in daily behavior. Meanwhile, work readiness is a condition of harmony between physical, mental and experience abilities and a person's capacity to complete a job in accordance with certain provisions. The sample of this research is 97 students of SMKN 1 Kendari. The measuring instrument used in this study is the self-confidence scale and work readiness scale using the Likert scale method. The self-confidence scale has a reliability value (rxy) = 0.937 consisting of 18 items, while the work readiness scale has a reliability value (rxy) = 0.945. The analysis of this study uses the Pearson product moment correlation. Based on the results of the analysis, it was found that there is a positive relationship between self-confidence and work readiness with a value of r = 0.8622, with sig = 0.000. This shows that the higher the self-confidence, the higher the job readiness.